2013
DOI: 10.1016/j.transproceed.2013.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplantation Systemic Immunomodulation with SA-FasL–Engineered Donor Splenocytes Has Robust Efficacy in Preventing Cardiac Allograft Rejection in Mice

Abstract: Apoptosis induced by the engagement of FasL with Fas receptor on the surface of lymphocytes is an important immune homeostatic mechanism that ensures tolerance to self-antigens under normal physiologic conditions. As such, FasL has been extensively tested as a tolerogenic molecule with the use of gene therapy in settings of autoimmunity and transplantation with conflicting outcomes. Although the mechanistic basis of these contradictory observations is largely unknown, the use of wild-type FasL and the means by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Szabolcs, Matthias J. gave the conclusion that apoptosis is a major form of myocyte death during human cardiac allograft rejection [5,9]. Considering that postmitotic cardiac myocytes have a limited capacity to regenerate compared with embryonic and neonatal cardiac myocytes, cardiac myocyte apoptosis becomes a significant factor contributes to graft failure during cardiac rejection [6][7][8]39,40]. The activation of intrinsic and extrinsic apoptotic pathways converge at the level of activation of caspase-3, which is one of the pivotal points in the apoptotic cascade [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Szabolcs, Matthias J. gave the conclusion that apoptosis is a major form of myocyte death during human cardiac allograft rejection [5,9]. Considering that postmitotic cardiac myocytes have a limited capacity to regenerate compared with embryonic and neonatal cardiac myocytes, cardiac myocyte apoptosis becomes a significant factor contributes to graft failure during cardiac rejection [6][7][8]39,40]. The activation of intrinsic and extrinsic apoptotic pathways converge at the level of activation of caspase-3, which is one of the pivotal points in the apoptotic cascade [39].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of cardiac myocytes, myocardial inflammation and contractile dysfunction are considered to be the hallmarks of cardiac allograft rejection [5][6][7][8][9]. Recent reports have shown that both innate and adaptive immunity contribute to acute organ transplant rejection, which affects allograft survival a lot [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…This method demonstrated protection against and rever-sal of EAE out to 245 days and prevented the onset of T1D in NOD mice out to 210 days. 192 We previously discussed the Shirwan group's presentation of FasL on biomaterials to prevent allograft rejection, and they have also used their streptavidin (SA) binding system to modify splenocytes [193][194][195][196] and pancreatic islets. 197,198 SA-FasL-decorated splenocytes inhibited primary and secondary alloreactive responses by blocking proliferative responses and inducing apoptosis of lymphocytes.…”
Section: Reviewmentioning
confidence: 99%
“…Heart grafts that received SA-FasL-decorated splenocytes intraperitoneally on days 1, 3, and 5 post-transplantation with a 15-day daily dose of rapamycin, achieved graft acceptance for the duration of observation (100 days). 194,195 The Shirwan and Yolcu team have used the streptavidinbiotin affinity mechanism to decorate cells with other immunomodulatory proteins, such as CD47 199 and PD-L1. 200,201 CD47 protein is an innate immune checkpoint signal that provides "don't-eat-me" self-recognition signals.…”
Section: Reviewmentioning
confidence: 99%